General overview of Tillandsia subgenus Tillandsia in Peru: The three-pinnate species and the case of two endemic species - León, Blanca (2008)
A recent collection of a specimen with three-pinnate inflorescence was the inspiration to evaluate Tillandsia subgenus Tillandsia taxa with three pinnate inflorescences for the Peruvian flora. Tillandsia extensa characteristics are clarified, confirming its distribution for northeastern Peru, and recognizing a specimen, previously considered being the second record for this species, as T. platyphylla.